Analysis of Genetic Diversity in three Kazakh Sheep using 12 Microsatellites - Dossybayev, Kairat; Mussayeva, Aizhan; Bekmanov, Bakytzhan; Kulataev, Beibit (International Journal of Engineering and Technology, 2018)
The genetic structure of three Kazakh sheep breeds was examined by using 12 microsatellite loci. A total of 144 alleles were detected from the 12 STR loci, with a mean value of 12.0. The highest allele diversity was found at the locus CSRD247 (16 alleles). PIC value showed that all studied STR markers are more informative and appropriate for genetic analysis of three Kazakh sheep populations. Beside of INRA006, all markers had high level of genetic variability. As Fixation index shows, the excess of the heterozygosity was observed only in loci MAF065. Obtained number of private alleles in Edilbai, Kazakh Arkhar Merino and Kazakh Fine-wool sheep were 25, 17 and 15 respectively. Genetic diversity was higher in Edilbai population than in other two populations. The genetic variability was lower in Kazakh Arkhar Merino sheep than in the Edilbai and Kazakh Fine-wool sheep breeds. The genetic distance was the largest between Edilbai and Kazakh Arkhar Merinos. Also, the moderate differentiation was observed between Edilbai and Kazakh Arkhar Merinos. Â Â Â